Enhancing the research enterprise at a health sciences university: A call for an institutional paradigm shift - Bryan G. Beutel; Taryn Bissing; Aaditya Patel; Nicolette Duong; Jan Talley (Journal of Education and Health Promotion)
Background: There exists a rapidly growing need for a universally robust research enterprise at health sciences universities because of recent changes in the medical education landscape. This study aimed to evaluate student perceptions of (and challenges conducting) research and to implement effective strategies to expose students to enhanced resources and training. Materials and Methods: An anonymous survey developed using participatory research methods was disseminated to all students at a graduate health sciences university in 2023. This measured their engagement in research, resource needs, and barriers. Descriptive statistics quantitively analyzed factors that influence student participation in research, perceived benefits, and obstacles to performing research. Content analyses of open-ended responses outlined strategies to improve the research endeavor. Results: Of 580 responses, the vast majority (78%) were “interested” or “very interested” in performing research, but only 36% were actively engaged in projects. The most commonly cited benefit of research was to improve competitiveness for future training opportunities (431 [18%] responses). Frequently listed barriers to conducting research were lack of time within the curriculum (290 [27%] responses), inadequate institutional support (278 [26%]), and faculty unavailability (207 [19%]). Students proposed multiple initiatives to enhance research infrastructure, including a central communication website to exchange research ideas, expansion of research mentors and opportunities/partnerships, and hiring research-focused support staff. Conclusions: A critical need exists at health sciences universities for a shift toward universal recognition of the need for an enhanced research enterprise that addresses key barriers to student engagement. This study proposes strategies to achieve an active research model.